The investigation of the NH3-SCR performance of a copper-based AEI-CHA intergrown zeolite catalyst - Ye, Hongling; Ren, Kai; Wang, Pengfei; Wang, Lin (Frontiers in Chemistry, 2022)
This work prepared an ISAPO-34/SAPO-18 intergrown zeolite using phosphate organoamine as the structure guiding agent. Physical-chemical characterizations by XRD, SEM, TG, and BET showed that the SAPO-34/SAPO-18 presents a cross-stacked cubic block-like microscopic morphology, with characteristic diffusive diffraction peaks at 2θ = 16–18° and 30–33° and a specific surface area of 557 m2 g−1. The series of copper-based catalysts prepared from SAPO-34/SAPO-18 showed a shift of the active temperature window to a lower temperature with increasing copper content. Moreover, the Brønsted acid site decreased significantly due to copper ion exchange and zeolite structure framework damage. Among them, the 1.2 wt% sample showed the widest active temperature window, with a T90 range of 175–435°C. After low-temperature hydrothermal aging treatment, the zeolite structure was eroded and the catalyst activity deteriorated significantly.